Bibliometric Exploration of Factors Affecting Community Involvement in Environmental Law Enforcement - Judijanto, Loso; Lubis, Arief Fahmi; Arini, Rani Eka (Westscience Press, 2024)
This research conducts a comprehensive bibliometric exploration to unravel the factors influencing community involvement in environmental law enforcement, a critical aspect of safeguarding ecosystems and public health. Environmental law enforcement relies heavily on community participation, yet understanding the determinants shaping such involvement remains incomplete. Through a systematic analysis of scholarly literature, this study aims to bridge this gap by identifying key themes, trends, and gaps in understanding community dynamics in environmental law enforcement contexts. The research employs bibliometric techniques to analyze a vast corpus of publications, exploring factors such as social norms, economic conditions, and enforcement strategies affecting community engagement. The findings not only contribute to theoretical understanding but also offer practical insights for policymakers, environmental agencies, and community organizers to enhance community participation in environmental protection efforts.